HSP90-regulated CHIP/TRIM21/p21 Axis Involves in the Senescence of Osteosarcoma Cells - Xu, Gui-Sheng; Lin, Yu-Ning; Zeng, Qingzhong; Li, Zhi-Peng; Xiao, Teng; Ye, Yong-Sheng; Li, Zhen-Yan; Gao, Xuejuan (Protein and Peptide Letters, 2023)
Background: OS is the most frequent malignant bone tumor with a poor prognosis. TRIM21 has been reported to play a critical role in OS by regulating the expression of the TXNIP/p21 axis and inhibiting the senescence of OS cells. Aim: Investigation of the molecular mechanism of tripartite motif 21 (TRIM21) in osteosarcoma (OS) would shed light on the understanding of the pathogenesis of OS. Objective: This study aimed to explore the mechanism regulating the protein stability of TRIM21 in the process of OS senescence. Methods: Human U2 OS cells were used to establish stable cells overexpressing TRIM21 (induced by Dox) or knocking down TRIM21. The co-immunoprecipitation (co-IP) assay was used to examine the interaction between TRIM21 and HSP90. Immunofluorescence (IF) assay was used to observe colocalization in OS cells. Western blot analysis was applied to detect the protein expression, and quantitative real-time PCR (qRT-PCR) assay was used to test the mRNA expression of corresponding genes. SA-β-gal staining was used to evaluate OS senescence. Results: In this study, we verified the interaction between HSP90 and TRIM21 using a co-IP assay. Knockdown or inhibition of HSP90 with its inhibitor 17-AAG accelerated the degradation of TRIM21 by the proteasome in OS cells. CHIP E3 ligase mediated this degradation of TRIM21, with the knockdown of CHIP rescuing the downregulation of TRIM21 induced by 17-AAG. TRIM21 inhibited OS senescence and downregulated the expression of senescence marker p21, while CHIP exhibited an opposite regulatory role on p21 expression. Conclusion: Taken together, our results demonstrated that HSP90 is responsible for the stabilization of TRIM21 in OS and that the CHIP/TRIM21/p21 axis controlled by HSP90 affects the senescence of OS cells.
Keywords: CHIP